2019
DOI: 10.1101/771410
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coagulopathy signature precedes and predicts severity of end-organ heat stroke pathology in a mouse model

Abstract: Text word count: 3,988; Abstract word count: 250; Number of figures: 5; Number of tables: 0; Number of references: 32 Scientific category: Thrombosis and HemostasisKey points:• A signature of pro-coagulation markers predicts circadian core body temperature and levels of organ damage in heat stroke • Changes in coagulopathy-related gene expression are evidenced before histopathological organ damage AbstractHeat stroke is a life-threatening condition characterized by loss of thermoregulation and severe elevation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Therefore, COVID-19 coagulopathy does not lead to a bleeding state, but to a thrombotic state (Pryzdial et al, 2020). Although the role of anticoagulant therapy in inhibiting progression of disease and reducing death is not yet clear, most hospitals have begun to use preventive medium doses or even therapeutic doses of anticoagulant therapy for specific patients to prevent potential thrombosis complications (Patel and Sengupta, 2020;Proctor et al, 2020;Yin et al, 2020b). The study by Liu et al (2020c) demonstrated that when treated with heparin molecules, not only did heparin act as an anticoagulant, but it also bound to the SARS-COV-2 spike protein, preventing the virus from binding to the receptor cells.…”
mentioning
confidence: 99%
“…Therefore, COVID-19 coagulopathy does not lead to a bleeding state, but to a thrombotic state (Pryzdial et al, 2020). Although the role of anticoagulant therapy in inhibiting progression of disease and reducing death is not yet clear, most hospitals have begun to use preventive medium doses or even therapeutic doses of anticoagulant therapy for specific patients to prevent potential thrombosis complications (Patel and Sengupta, 2020;Proctor et al, 2020;Yin et al, 2020b). The study by Liu et al (2020c) demonstrated that when treated with heparin molecules, not only did heparin act as an anticoagulant, but it also bound to the SARS-COV-2 spike protein, preventing the virus from binding to the receptor cells.…”
mentioning
confidence: 99%
“…Severe heatstroke would lead to multiple organ dysfunction and death. For example, Proctor and other studies found that when mice were exposed to 39.5 ℃ would cause coagulation dysfunction [14]; Zhou et al found that when rats were exposed to a simulated desert environment (41℃), the liver (AST, ALT), kidney (BUN, Crea), heart (CK-MB, CK kinase) and lung function (BEecf, HCO3 − ) were signi cantly damaged. At the same time, the morphology and structure of liver, kidney, heart, and lungs were changed signi cantly after heatstroke, and as the duration of heatstroke prolong, the damage to organ function was aggravated [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, more specific and reliable biomarkers are needed. Proctor et al 44 demonstrated increased D-dimer and soluble thrombomodulin levels in a severe non-exertional heatstroke mouse model. Bouchama et al 59 compared the levels of thrombin-antithrombin complex, fibrin monomers, plasminantiplasmin complex, and D-dimer between heatstroke and heat-illness at hospital presentation.…”
Section: Biomarkers and Diagnosismentioning
confidence: 99%
“…43 Similarly, even if the global coagulation markers do not change significantly, HSIC may be diagnosed by increased levels of sensitive coagulation biomarkers such as D-dimer, thrombin-antithrombin complex, and soluble thrombomodulin. 44…”
Section: Figure 3 Classification Of Coagulopathymentioning
confidence: 99%